A coupled chlorinase–fluorinase system with a high efficiency of trans-halogenation and a shared substrate tolerance. Issue 68 (7th August 2018) - Sun, H.; Zhao, H.; Ang, E. L.
Abstract : SAM-dependent chlorinases exhibited tolerance to the modification at the C-2 position of the adenosine substrate and acted cooperatively with fluorinase for rapid trans -halogenation. Abstract : Enzymatic trans -halogenation enables radiolabeling under mild and aqueous conditions, but rapid reactions are desired. We developed a coupled chlorinase–fluorinase system for rapid trans -halogenation. Notably, the chlorinase shares a substrate tolerance with the fluorinase, enabling these two enzymes to cooperatively produce 5′-fluorodeoxy-2-ethynyladenosine (5′-FDEA) in up to 91.6% yield in 1 h.